Development Of Biodegradable Plastics For Packaging Using Wastes From Oil Palm And Sugar Cane - Wahid, Mohammad Khalid; Ahmad, Mohd Nazri; Osman, Mohd Hairizal; Maidin, Nurul Ain; Ab Rahman, Mohd Hidayat; Hussin, Mohamed Saiful Firdaus; Kasno, Mohammad `Afif (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
This paper presents the comparison of tensile strength and biodegradable test of three different biodegradable plastics made from tapioca starch that mixture with natural fiber such as oil palm fiber and sugar cane fiber. The application of this research is to produce biodegradable plastic packaging for the food industry purpose. Tapioca starch is used as the main ingredient with sugar cane fiber and oil palm fiber mixture and prepared in three different variation. The tensile strength test followed the ASTM D638 standard shown that biodegradable plastic produced with tapioca starch and oil palm fiber had highest tensile strength with 1.122 MPa as compared to biodegradable plastic with tapioca starch and sugar cane fiber that only obtained at 0.290 MPa. However, the combination of the mixture fiber had showed significant improvement at 0.33 MPa. Then these biodegradable plastic is evaluated with biodegradable test followed with ASTM-6400-99 standard.